Frugal Innovation as a Mediating Mechanism between Strategic Flexibility, Sustainability Orientation, and Operational Performance - Labanie, Achmad; Pusparini , Elok Savitri (Economics, Business, Accounting & Society Review, 2026)
Recent studies recognize innovation as a critical pathway for strengthening SME competitiveness and resilience. This study investigates how food and beverage SMEs improve operational performance by transforming strategic flexibility and sustainability orientation into practical, cost-efficient innovation practices. In highly competitive and resource-constrained environments, SMEs must balance efficiency, adaptability, and increasing sustainability expectations. The research focuses on frugal innovation as a pragmatic approach that emphasizes simplicity, affordability, and optimal resource utilization in daily operations. A quantitative research design was employed using survey data collected from owners and operational managers of food and beverage SMEs in the Jabodetabek region. The constructs were measured using established Likert-scale instruments adapted from prior studies. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), which enables simultaneous assessment of measurement reliability and structural relationships among variables. This approach allows for examining both direct and indirect effects within a mediation framework. The findings indicate that strategic flexibility and sustainability orientation contribute to the development of frugal innovation practices. In turn, frugal innovation significantly enhances operational performance by improving efficiency, reducing operational waste, and strengthening process effectiveness. The results confirm that performance improvements emerge when strategic intentions are translated into concrete, resource-aware innovations. This study contributes by providing empirical evidence that frugal innovation serves as a practical mechanism linking strategic orientation to superior operational outcomes in resource-constrained SMEs.